Ascorbate and phagocyte function. - Stankova, L (1975)
Scorbutic guinea pig neutrophils (PMN) were found to produce H2O2 and kill Staphylococcus aureus as well as control PMN, suggesting that ascorbate does not contribute significantly to phagocyte H2O2 production or bacterial killing. Total and reduced ascorbate contents of human PMN was observed to fall upon phagocytosis, whereas dehydroascorbate increased to a lesser extent. These observations are consistent with the view that ascorbate constitutes a functional part of the PMN's redox-active components and may thus function to protect cell constituents from denaturation by the oxidants produced during phagocytosis.